TO CREATE DNA BARCODE DATA OF MAGNOLIA CHEVALIERI (DANDY) V.S. KUMAR FOR IDENTIFICATION SPECIES AND RESEARCHING GENETIC DIVERSITY - Van Huan, Ha; Thi Thao Nguyen, Luu; Minh Quang, Nguyen (Journal of Forestry Science and Technology, 2018)
To create the nucleotide sequence of DNA barcode database, they are usually used as a DNA barcode to identify species and research of genetic diversity in plants. In this study, the genomic DNA was extracted from leaf tissue of Magnolia chevalieri (Dandy) V.S. Kumar. The DNA barcodes (matK, rbcL, trnH-psbA, ITS2 and ycf1b) were amplified from total DNA of Magnolia chevalieri (Dandy) V.S. Kumar by PCR technique. DNA sequencing by Sanger method and performed on an automated DNA sequencer. The DNA sequences were analyzed using software programs such as Mega6, BioEdit, GeneDoc, DNAClub and ClustalX. The PCR results indicated that all DNA bands were amplified from the samples, they have the same size similar to the theoretical size of matK, rbcL, trnH-psbA, ITS2 and ycf1b. Nucleotide sequence analysis of PCR product samples showed that the size of the isolated matK gene fragment is 768 bp, rbcL fragment is 599 bp, trnH-psbA fragment is 512 bp, ITS2 fragment is 406 bp and ycf1b fragment is 1005 bp. The above nucleotide sequences were compared with the nucleotide sequences in the international gene bank NCBI, the highest level of similarity as follows: the matK fragment and rbcL fragments compared with Magnolia conifera var. chingii species with 99.73% similarity and 99.63% similarity, respectively; the trnH-psbA compared with Magnolia conifera var. chingii pecies with 99.22% similarity and they cf1b fragment compared with Magnolia officinalis subsp. Biloba species 99.5% similarity. The nucleotide sequences of matK, rbcL, trnH-psbA, ITS2 and ycf1b from Magnolia chevalieri (Dandy) V.S. Kumar have been registered on the DNABank.vn with Barcode ID MMC0001, MMC0002, MMC0003, MMC0004 and MMC0005. Recommendation for using ITS2 andtrnH-psbA marker as DNA barcode to identify Magnolia chevalieri (Dandy) V.S. Kumar species.